EXPERIENCE OF CREATIVE INTERNATIONAL COOPERATION WITHIN THE FRAMEWORK OF THE UKRAINE-AUSTRALIA RESEARCH FUND - MIKHAILENKO, V.; KUCHEL, P. (PH Akademperiodyka, 2024)
Science and politics have always gone together. This is what happened in our days when Russia's military aggression against Ukraine, which began in 2014, turned into a full-scale military invasion in 2022 and a war of liberation for the independence and freedom of Ukraine. These events dramatically affected not only the fate of millions of citizens but also brought the destruction of fields of science and technology important for the existence of the country.